Elevated serum homocysteine levels in paediatric patients with primary Raynaud's phenomenon - Kutilek, Stepan; Nemec, Vladimir; Bockayova, Eva (Revista brasileira de reumatologia, 2012)
INTRODUCTION: Raynaud's phenomenon (RP) is a paroxysmal and recurrent acral ischemia resulting from an abnormal arterial vasospastic response to cold or emotional stress. Homocysteine, a sulphured amino acid, has been linked to cardiovascular and neurodegenerative diseases, diabetes, thrombosis, and bone fragility. Homocysteine has been also linked to the pathogenesis of RP, as increased serum homocysteine (S-homocysteine) levels were observed in patients with RP. OBJECTIVE: As all publications concerning S-homocysteine in RP involved only adult patients, our aim was to evaluate S-homocysteine in children and adolescents with RP. METHODS: Nineteen patients (two boys and 17 girls; mean age 16.1 ± 2.2 SD) with primary RP were enrolled. The controls were 51 children and adolescents (21 boys and 30 girls; mean age 15.1 ± 1.8 SD). RESULTS: The S-homocysteine level was significantly higher in the RP group in comparison with controls (11.2 ± 2.4 vs. 8.0 ± 2.0 µmol/L; P = 0.00001). S-homocysteine levels in RP were not age-dependent. CONCLUSION: Paediatric patients with RP have increased S-homocysteine levels, suggesting that homocysteine plays an important role in the development of vascular dysfunction, even at an early age.
Keywords: dítě; Homocysteine; Adolescent; mladiství; mužské pohlaví; homocystein; Raynaudova nemoc; ženské pohlaví; lidé; Child; Raynaud Disease; Young Adult; Humans; mladý dospělý; Male; Female